Study on Phytochemical, Antibacterial, Antioxidant and Toxicity Profile of Viscum album Linn Associated with Acacia catechu - Kusi, Meena; Shrestha, Kanti; Malla, Rajani (Nepal Journal of Biotechnology, 2015)
This study focuses on antibacterial, antioxidant and toxic potentials of Viscum album Linn, commonly known as European mistletoe associated with Acacia catechu (Khayer in Nepali). Methanol extract of the aerial parts of the Mistletoe was prepared by cold percolation method. The resulting extract was simultaneously subjected to phytochemical screening; anti-microbial activity; anti-oxidant potential and Brine shrimp toxicity test. The major biologically active phyto-constituents observed were alkaloids, glycosides, saponins, polyphenols, flavonoids, tannins, terpenoids and cardiac glycosides. Upon antibacterial activity screening, the plant extract was found to be highly effective against Pseudomonas aeruginosa with the zone of inhibition 16±1mm compared to 17±1mm of chloramphenicol (50 mcg). The antioxidant activity as EC50 value by DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging activity was found to be 1.58 mg/ml while the ferric reducing capacity was measured to be 282.83±19.55 mg FeSO4.7H2O eqvt/g dry wt. of the extract during Ferric Ion Reducing Antioxidant Power (FRAP) Assay. The LC50 value for Brine Shrimp Toxicity Assay was found to be 31.62 ppm. This study shows the medicinal value of the mistletoe associated with Acacia catechu. Further meticulous analysis of this plant might lead to identification of active biomolecules effective as drugs for various ailments Nepal Journal of Biotechnology. Dec. 2015 Vol. 3, No. 1: 60-65